Prevalence and mechanism of injuries in male beach soccer player - reza sharifatpour; mahdieh akoochakian; Mohammad Hossein alizadeh; Hamid abbassi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: One of the preventing injuries methods is recognizing common injuries in sports and causative factors of injury. The aim of this study was to investigate the prevalence and mechanism of injury in professional beach soccer players in Yazd province. Methods: The present study is a survey-descriptive research that was conducted as a field study. Number of 40 players currently in the premier league country were selected as samples. For collecting information, the modified injury report questionnaire by Fuller et al. (2006) was used. Data were analyzed by using chi-square test at a significance level P < 0.05. Results: The results showed that the most common injuries were in lower extremities (%69.84) and in terms of injury severity, 31.75% were sever injury, and for type of injuries, strain was the most of the injuries occurred (%33.33). The amount of injury during the match (60.26%) was higher than the time of training (39.68%). The degree of contact injuries 73.02% was significantly higher than non-contact injuries 26.98% (p <0.05). Conclusion: Most of the injuries in this sport are caused by lack of the shoes and guards on the legs and feet, and then on the knee. Contact of players is one of the main sources of injury in beach soccer, which is likely to be effective in preventing injury by changing training, implementing proper techniques, and improving performance factors by using injuries preventive programs.